Enhanced removal of metronidazole from aqueous solutions via photo-Fenton-like process: efficiency, kinetics, and toxicity assessment - Saeid Babaei; Farokh Rokhbakhsh-Zamin; Mohammad Ahmadian; Davood Kalantar-Neyestanaki; Nadia Kazemipour (Applied Water Science)
Abstract The current study investigated the degradation of the antibiotic metronidazole (MNZ) from aqueous solutions by means of a photo-Fenton-like process-based system. The efficiency of each variable such as CuCOFe2O4@AC nanoparticles (CFC), UV, and H₂O₂, along with their combined processes, was evaluated to select the most appropriate integrated process. In the second stage, a toxicity test was conducted to assess the drug residues in the effluent from the process. The toxicity test was conducted using the penetration method in Mueller-Hinton agar medium by inoculating wells and blank disks impregnated with the treated wastewater samples and control samples. The removal efficiencies of MNZ for UV, H₂O₂, CFC, UV + H₂O₂, CFC + H2O2, and UV + CFC + H₂O₂ processes were 2.28, 2.35%, 22.76, 7.53, 34.32, and 24.04%, respectively. As a result, the Fenton-like process (CFC + H2O2) was identified as the most effective method. Under test conditions: pH equal to 5, hydrogen peroxide value 1000 mg/L, CFC dosage 1000 mg/L, initial MNZ content 10 mg/L, and contact time 70 min, 67.5% of the antibiotic was removed. It was found that the effluent pharmaceutical residues were non-toxic to Escherichia coli and Enterococcus faecalis bacteria. The kinetic studies for the Fenton-like process indicated that the second-order model best fitted the achieved results. Moreover, synergistic effect in the combination process was 1.86 times greater than that of the individual processes. Also, the process demonstrated favorable efficiency in removing MNZ from aqueous solutions. Since the treated wastewater is non-toxic and the nanoparticles can be magnetically recovered, this method appears to be a promising solution for the pharmaceutical industry.